Respon Pertumbuhan dan Produksi Jintan Hitam (Nigella sativa L.) dengan Pemupukan Nitrogen dan Fosfor - Suryadi, Rudi; Ghulamahdi, Munif; Kurniawati, Ani (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2015)
ABSTRACTBlack cumin (Nigella sativa L.) is a native medicinal plant to subtropical West Asia and the Mediterranean regions. So far, information regarding black cumin fertilization is still limited. The objectives of this study was to obtain the optimum rate of N and P fertilizer in order to promote the growth and production of black cumin under tropical climates. This research was conducted at Manoko Experimental Station, Lembang, West Java from October 2012 to January 2013. The research was arranged in randomized complete block design with two factors and three replications. The first factor was four rates of N fertilizer (0, 40, 80, 120 kg N ha-1), and the second factor was four rates of P fertilizer (0, 40, 80, 120 kg P2O5 ha-1). The results showed that application of N and P fertilizers increased plant height, leaf number, branch number, leaf area, leaf area index, relative growth rate, net assimilation rate, plant dry weight, number of capsule per plant, number of seed per capsule, seed weight per plant, and weight of 1,000 seeds. Moreover, growth and production of black cumin still increased at the highest rates of N and P fertilizers, therefore, it is necessary to study for N and K at higher rates in order to obtain optimum production rate.Keywords: medicinal plant, rate of fertilizer, tropical